Perkembangan Ruang Sosial Kota: Studi Antropologi Perkotaan pada Pola Interaksi Masyarakat Urban Makassar - Kesuma, Andi Ima (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
The transformation of social spaces in urban areas is a complex phenomenon shaped by development dynamics, migration flows, economic changes, and policy interventions. This article examines the shifting structure and function of social spaces in Makassar City, South Sulawesi, and how these shifts influence patterns of interaction among urban communities from an urban anthropological perspective. Using a qualitative approach, this study employs participant observation, in-depth interviews, and document analysis in several key areas, including dense residential neighborhoods, public spaces, and centers of informal economic activity. The findings reveal that urbanization and modernization have driven a transition from collective communal interaction patterns toward more individualistic and functional ones. Nevertheless, communities exhibit creative adaptations to these changes by forming new social groups, utilizing space flexibly, and maintaining localized practices of solidarity. This article highlights the importance of integrating cultural and social dimensions in urban planning to ensure that urban spaces remain inclusive and support social cohesion. The findings contribute to the development of urban anthropological theory and provide valuable insights for designing socially equitable urban development policies.